2016
DOI: 10.1186/s13059-016-0955-7
|View full text |Cite
|
Sign up to set email alerts
|

Genomic screens identify a new phytobacterial microbe-associated molecular pattern and the cognate Arabidopsis receptor-like kinase that mediates its immune elicitation

Abstract: BackgroundThe recognition of microbe-associated molecular patterns during infection is central to the mounting of an effective immune response. In spite of their importance, it remains difficult to identify these molecules and the host receptors required for their perception, ultimately limiting our understanding of the role of these molecules in the evolution of host-pathogen relationships.ResultsWe employ a comparative genomics screen to identify six new immune eliciting peptides from the phytopathogenic bac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
59
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(59 citation statements)
references
References 52 publications
0
59
0
Order By: Relevance
“…These findings directly led to the discovery of flgII-28 as a pattern recognized by LRR-RK FLS3 (see below) and Ave1 as an effector recognized by LRR-RLP Ve1 in tomato plants. Most recently, this approach was applied to identify six new peptides, including xup25, from Pseudomonas syringae that trigger immune responses in Arabidopsis (Mott et al, 2016). This important work further illustrates the power of the comparative genomics approach in revealing novel microbial patterns and in isolating their corresponding PRRs.…”
Section: Innovative Approaches To Identify Microbial Patterns/apoplasmentioning
confidence: 99%
“…These findings directly led to the discovery of flgII-28 as a pattern recognized by LRR-RK FLS3 (see below) and Ave1 as an effector recognized by LRR-RLP Ve1 in tomato plants. Most recently, this approach was applied to identify six new peptides, including xup25, from Pseudomonas syringae that trigger immune responses in Arabidopsis (Mott et al, 2016). This important work further illustrates the power of the comparative genomics approach in revealing novel microbial patterns and in isolating their corresponding PRRs.…”
Section: Innovative Approaches To Identify Microbial Patterns/apoplasmentioning
confidence: 99%
“…Therefore, fliC probably evolves neutrally in R. solanacearum because all extant R. solanacearum fliC alleles are derived from an ancestral allele that had already evolved to escape recognition. Another P. syringae PAMP that was not flagged in our screen and for which the R. solanacearum allele was not found to trigger any ROS was Xup 25 (Mott et al ., ) (Fig. and Table ).…”
Section: List Of the Core Genes Of The 37 Ralstonia Solanacearum Stramentioning
confidence: 88%
“…() and Mott et al . (), which is based on the hypothesis that PAMPs are encoded by core genome genes that are under selection to escape recognition by plant PRRs. We decided to identify core genome genes that do not evolve neutrally by calculating Tajima's D , which is a measure of deviation from neutral evolution (Tajima, ).…”
Section: List Of the Core Genes Of The 37 Ralstonia Solanacearum Stramentioning
confidence: 99%
“…Furthermore, the identification of various PRRs for chemically diverse types of MAMPs has revealed that plant PRRs are typically RLKs or RLPs. Thus, these protein families can now also be systematically tested for a putative role in plant immunity, for instance through screening for altered resistance against the pathogen of interest in loss-or gain-of-function mutants or natural accessions, or through heterologous expression in suitable model plants (e.g., Arabidopsis thaliana or N. benthamiana) [64][65][66][67][68][69].…”
Section: Prr Engineeringmentioning
confidence: 99%